A Pseudomonas putida strain genetically engineered for 1,2,3-trichloropropane bioremediation - Samin, Ghufrana; Pavlova, Martina; Arif, M Irfan; Postema, Christiaan P; Damborsky, Jiri; Janssen, Dick B (Applied and environmental microbiology, 2014)
1,2,3-Trichloropropane (TCP) is a toxic compound that is recalcitrant to biodegradation in the environment. Attempts to isolate TCP-degrading organisms using enrichment cultivation have failed. A potential biodegradation pathway starts with hydrolytic dehalogenation to 2,3-dichloro-1-propanol (DCP), followed by oxidative metabolism. To obtain a practically applicable TCP-degrading organism, we introduced an engineered haloalkane dehalogenase with improved TCP degradation activity into the DCP-degrading bacterium Pseudomonas putida MC4. For this purpose, the dehalogenase gene (dhaA31) was cloned behind the constitutive dhlA promoter and was introduced into the genome of strain MC4 using a transposon delivery system. The transposon-located antibiotic resistance marker was subsequently removed using a resolvase step. Growth of the resulting engineered bacterium, P. putida MC4-5222, on TCP was indeed observed, and all organic chlorine was released as chloride. A packed-bed reactor with immobilized cells of strain MC4-5222 degraded >95% of influent TCP (0.33 mM) under continuous-flow conditions, with stoichiometric release of inorganic chloride. The results demonstrate the successful use of a laboratory-evolved dehalogenase and genetic engineering to produce an effective, plasmid-free, and stable whole-cell biocatalyst for the aerobic bioremediation of a recalcitrant chlorinated hydrocarbon.
Keywords: exprese genu; Gene Expression; Recombinant Proteins; Plasmids; Biodegradation, Environmental; Biotransformation; Metabolic Engineering; látky znečišťující životní prostředí; Pseudomonas putida; propan; transpozibilní elementy DNA; Hydrolases; hydrolasy; Propane; Selection, Genetic; rekombinantní proteiny; selekce (genetika); biotransformace; DNA Transposable Elements; metabolické sítě a dráhy; metabolické inženýrství; plazmidy; Environmental Pollutants; Metabolic Networks and Pathways; biodegradace